Effect of Anabolic–Androgenic Steroid Abuse on the Contact Activation System - Sidelmann, Johannes Jakobsen; Gram, Jørgen Brodersen; Palarasah, Yaseelan; Rasmussen, Jon Jarløv; Kistorp, Caroline (Thrombosis and Haemostasis, 2021)
The effect of anabolic–androgenic steroid (AAS) abuse on the contact activation system (CAS) is not known in detail. We hypothesized that current AAS abuse reduces the kallikrein-generating capacity of CAS significantly and investigated the impact of AAS on the proteins and capacity of CAS in current and former AAS abusers and healthy age-matched controls. Men 18 to 50 years of age were included as current AAS abusers, former AAS abusers, or controls. Blood samples were collected after overnight fasting. Kallikrein generation (lag time, peak height, and endogenous kallikrein potential [EKP]), coagulation factor XII (FXII), prekallikrein, high-molecular-weight kininogen (HK), and Complement C1 esterase inhibitor (C1inh) were assessed. Groups were compared by analysis of variance or Kruskal–Wallis test and probabilities were corrected for multiple comparisons. Associations were evaluated by linear regression models. The EKP was significantly reduced in current (n = 37) AAS abusers (984 ± 328 nmol/L × min) compared with former (n = 33) abusers (1,543 ± 481 nmol/L × min) and controls (n = 30) (1,521 ± 339 nmol/L × min), p < 0.001. Current abusers had higher levels of FXII and C1inh and lower levels of prekallikrein and HK than controls, p ≤ 0.025. Stepwise regression analysis showed that EKP was associated with C1inh and prekallikrein in current AAS abusers, R2 = 0.70, p < 0.001. We conclude that current AAS abuse reduces the kallikrein-generating capacity of CAS by increasing the concentration of C1inh and reducing the concentration of prekallikrein. These changes may contribute to the anti-inflammatory effect of testosterone.
Keywords: factor XII; prekallikrein; C1 esterase inhibitor; high-molecular-weight kininogen; anabolic–androgenic steroids